Peningkatan Kapasitas Pengelolaan dan Pelaporan Dana Desa - Mochammad Ilyas Junjunan; Ajeng Tita Nawangsari (Universitas Muhammadiyah Yogyakarta, 2021)
The village fund law has mandated the government to allocate village funds for the welfare of the community in the village. Public understanding of the importance of accountability must be reported to the state is the main focus of this community service activity. This empowerment activity aimed to increase public understanding of the management and reporting funds in the Kebonsari Village, Candi, Sidoarjo Village. The program applied to learn by doing method in the form of practical learning. Activities were carried out in stages, including gathering information, implementing socialization training, mentoring, monitoring the management, and reporting activity funds for the community. The results showed an increase in the understanding and ability of community members in managing and reporting community activity funds in Kebonsari Village with entrepreneurial activities (salted eggs), handicrafts (Sayangan), and animal husbandry (Bebek Village). A total of 17 people out of 21 residents felt the beneficial impact of the activities was shown by the level of community satisfaction. Therefore, this activity should be promoted further with a different focus according to the problems found in the community to maintain and improve accountability culture by upholding the values of integrity and transparency in the management and reports of village funds in the future.